Risk of cellular or antibody-mediated rejection in pediatric kidney transplant recipients with BK polyomavirus replication: an international CERTAIN registry study - Fichtner, Alexander; Schmidt, Jeremy; Süsal, Caner; Carraro, Andrea; Oh, Jun; Zirngibl, Matthias; König, Sabine; Guzzo, Isabella; Weber, Lutz T.; Awan, Atif; Krupka, Kai; Schnitzler, Paul; et al. (Pediatric nephrology, 2025)
In kidney transplant recipients (KTR), BK polyomavirus-associated nephropathy (BKPyVAN) is a major cause of graft loss. To facilitate the clearance of BKPyV-DNAemia, reduction of immunosuppression is currently the treatment of choice but may increase the risk of graft rejection.
Online verfügbar: 11. Oktober 2024
Gesehen am 25.04.2025